PENGARUH ETNIK DALAM PEMBENTUKAN PARTI-PARTI POLITIK AWAL DI SARAWAK, 1959-1963: (THE INFLUENCE OF ETHNICITY IN THE FORMATION OF EARLY POLITICAL PARTIES IN SARAWAK, 1959-1963) - Anita Junaidi,; Noorlizawati Wan Mat Ali, (Jurnal Pengajian Melayu (JOMAS), 2023)
Abstract This paper discusses the influence of ethnicity in the formation of early political parties in Sarawak. The cession of Sarawak to the British government has led to the emergence of the people’s nationalism awareness leading to the formation of political parties in Sarawak. Discussion is done through the library method by analysing books, dissertation and articles by previous researchers. The results of this study found that the plurality of races in Sarawak played a significant role in shaping the political pattern in Sarawak. The evidence can be seen in the formation of political parties that are heavily influenced by racial elements. Thus, ethnic factors have become the main factor in the formation of political parties in Sarawak. This considering that the purpose of establishing the parties is to safeguard the interests of their respective races. Therefore, the influence of ethnicity in a party can be seen according to the composition of party membership which is dominated by certain races. However, there are also several other factors that influence the formation of early political parties in Sarawak. Among them are, differences in idealism, the effects of the 1956 municipal elections, the desire for independence, regional sentiments and the influence of a party's ideology. Overall, this study can disclose to the public that the racial nature has been rooted in political parties in Sarawak since the beginning. Therefore, it is suggested for the future studies, the researcher can analyse whether this race-based party has an impact on the political development in Sarawak. Keywords: ethnic influence, formation, political party, Sarawak, factor Abstrak Kajian ini membincangkan pengaruh etnik dalam pembentukan parti politik awal di Sarawak. Penyerahan Sarawak kepada British telah menyebabkan munculnya kesedaran nasionalisme dalam kalangan masyarakat di Sarawak sehingga membawa kepada pembentukan parti politik di Sarawak. Perbincangan dalam kajian ini dilakukan melalui kaedah kepustakaan dengan menganalisis buku, disertasi dan artikel-artikel pengkaji-pengkaji terdahulu. Hasil kajian ini mendapati kemajmukan kaum di Sarawak memainkan peranan besar dalam membentuk struktur politik di Sarawak. Buktinya dapat dilihat dalam pembentukan parti politik yang banyak dipengaruhi oleh unsur perkauman. Oleh sebab itu, faktor etnik telah menjadi faktor utama dalam pembentukan parti politik di Sarawak memandangkan tujuan penubuhan parti-parti tersebut adalah untuk menjaga kepentingan kaum masing-masing. Perkara ini dilihat dalam matlamat penubuhan parti-parti tersebut. Pengaruh etnik dalam sesebuah parti akan dapat dikesan melalui komposisi keahlian parti yang didominasi oleh kaum-kaum tertentu. Walau bagaimanapun, terdapat juga beberapa faktor lain yang mempengaruhi pembentukan parti politik awal di Sarawak seperti perbezaan idealisme, kesan pilihan raya perbandaran 1956, keinginan untuk merdeka, sentimen kedaerahan serta pengaruh ideologi sesebuah parti. Secara keseluruhannya, kajian ini dapat mendedahkan masyarakat bahawa sifat perkauman telah berakar umbi dalam parti-parti politik di Sarawak sejak dari awal lagi. Oleh itu, dicadangkan untuk kajian akan datang, pengkaji boleh mengupas sama ada parti berasaskan kaum ini memberi impak kepada perkembangan politik di Sarawak. Kata Kunci: pengaruh etnik, pembentukan, parti politik, Sarawak, faktor